Entering Career And Self Adaptation Of Female Sex Workersin RatchaburiI Province - Srisukphusap, Thaphatcharat (Journal of Humanities and Social Sciences Loei Rajabhat University, 2023)
The objectives of this research were to study individual factors, motivational factors entering into prostitution as well as self-adaptation of commercial female sex workers in Ratchaburi. 120 samples were drawn from the sex workers in Ratchaburi by stratified random sampling. The research instrument for data collecting was questionnaire designed by the researcher. The statistics for data analyzing were presented by percentage (%), mean ( ) , and standard deviation (S.D.). The findings of research were as follows: From the sample of commercial female sex workers in Ratchaburi, 36.7 percent were aged between 19-21 year. 40.8 percent entered the career aged between 19-21 years old. 53.3 percent had done primary level of education. 38.3 percent had domiciles/ residences/ home towns in the northern region. 44.2 percent were spouses/ partners who lived together without being married. 62.5 percent of the workplaces were brothels. 62.5 percent had been in the work for 1-3 years. Regarding their attitudes, the majority of female commercial sex workers admitted that the career was acceptable because it was from a condition of need for a temporary period. No one intended to enter into prostitution. They considered it could help their family finances. It was also an easy career which earned good income. They could help men for sexual release without any commitment. They could reduce family and social problems. But at the same time, some of the samples had an opposite opinion. They commented that it was a shameful, illegal, and immoral career. They had to hide from society and suffer for their whole life. They had to carry on being as prostitutes because they did not have enough knowledge to do any other occupation. The economic factors were the highest influence on motivation to enter into the prostitution. The cause was relevant to family factors such as poverty, cash requirements for themselves and their families, no supporter for their families but themselves, the perception that it was an easy way to earn good money, and it might be an opportunity to get a better life. Education factors were lack of educational opportunity, and low education level due to poor families’ inability to send their children to finish compulsory education. Besides, the factors of society, environment, values, and attitudes were related to the models of success from friends who persuaded them to enter the career. When someone did not succeed in her life, and were separated or divorced from spouses, the finally decided to get into prostitution. For self – adaptation of the commercial female sex workers, after young women had decided to enter into the prostitution, in order to survive in this career, they had to adapt themselves in many ways, respectively: compulsion to believe and follow such orders and regulations of the brothels, compulsion to make a good relationship with their colleagues, and acceptance of the career as well as making their life happy by purchasing various amenities such as TV, refrigerator, and mobile phone. They accepted various conditions that they had to trade for their goal such as having money and obtaining various amenities. So, they chose to adapt themselves in these ways so, which they could achieve their goal that was to have a lot of money in order to buy various goods; by which they thought those goods would make themselves honorable in society